"She must not stir out of a darkened room":: The Redpath Mansion Mystery - Adams, Annmarie; Minnett, Valerie; Poutanen, Mary; Theodore, David (Material Culture Review)

(untitled) (National Museums of Canada, 2010)
Abstract This paper accounts for private life in a prominent Gilded-Age Montreal bourgeois household as revealed in the sudden glare of publicity generated by a violent double shooting. We show how the tragic deaths of a mother and her son re-enforced fragile class connections between propriety and wealth, family relations and family image. Drawing on diaries, photographs and newspaper accounts, as well as published novels and poetry, we argue that the family deployed architecture, both the spaces of its own home and public monumental architecture in the city, to follow the dictates of a paradoxical imperative: intimacy had to be openly displayed, family private matters enacted in public rituals. The surviving family quickly began a series of manoeuvers designed to make secret the public event, and re-inscribe the deaths within class norms of decorum and conduct. The house itself, we claim, as a material object, figures in the complex interplay of inter-connected social relationships, behaviours and narratives that produce bourgeois respectability.